Importance of the intention-to-treat principle - Nagel, Simon; Haussen, Diogo C.; Nogueira, Raul G. (JAMA neurology, 2020)
To the Editor The recent study by Goyal et al1 represents the third largest cohort study on patients with large vessel occlusions (LVOs) who present with mild deficits (National Institutes of Health Stroke Scale score, 0-5) and, to our knowledge, the largest meta-analysis regarding this topic. This...